Healthcare utilization of Mexican-American Medicare beneficiaries with and without Alzheimer's disease and related dementias. - Brian Downer; Soham Al Snih; Mukaila Raji; Lin-Na Chou; Yong-Fang Kuo; Kyriakos S Markides; Kenneth J Ottenbacher (PLoS ONE)
Background Older adults with Alzheimer's disease and related dementias (ADRD) are high-risk to experience hospitalizations and emergency room (ER) admissions. Mexican-Americans have a high prevalence of ADRD, but there is limited information on the healthcare use of older Mexican-Americans with ADRD. We used data from a cohort of older Mexican-Americans that has been linked with Medicare files to investigate differences in hospitalizations, ER admissions, and physician visits according to ADRD diagnosis. We also identify sociodemographic, health, and functional characteristics that may contribute to differences in healthcare utilization between Mexican-American Medicare beneficiaries with and without an ADRD diagnosis. Methods and findings Data came from the Hispanic Established Populations for the Epidemiological Study of the Elderly that has been linked with Medicare Master Beneficiary Summary Files, Medicare Provider Analysis and Review files, Outpatient Standard Analytic files, and Carrier files. The final analytic sample included 1048 participants. Participants were followed for two years (eight quarters) after their survey interview. Generalized estimating equations were used to estimate the probability for one or more hospitalizations, ER admissions, and physician visits at each quarter. ADRD was associated with higher odds for hospitalizations (OR = 1.65, 95%CI = 1.29-2.11) and ER admissions (OR = 1.57, 95%CI = 1.23-1.94) but not physician visits (OR = 1.23, 95%CI = 0.91-1.67). The odds for hospitalizations (OR = 1.24, 95%CI = 0.97-1.60) and ER admissions (OR = 1.27, 95%CI = 1.01-1.59) were reduced after controlling for limitations in activities of daily living and comorbidities. Conclusions Mexican-American Medicare beneficiaries with ADRD had significantly higher odds for one or more hospitalizations and ER admissions but similar physician visits compared to beneficiaries without ADRD. Functional limitations and comorbidities contributed to the higher hospitalizations and ER admissions for older Mexican-Americans with ADRD.